PENGARUH FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, MANAGERIAL OWNERSHIP TERHADAP DIVIDEN POLICY MELALUI DEBT POLICY SEBAGAI PEMEDIASI - Luh Nik Oktarini; Putu Atim Purwaningrat (Widya Manajemen, 2019)
The purpose of this study was to determine the effect of free cash flow to debt policy to determine the influence of investment opportunity set against debt policy to determine the effect of managerial ownership on debt policy to determine the effect of free cash flow to the dividend policy to determine the effect of managerial ownership to dividend policy. This research was conducted on manufaktur companies listed in Indonesia Stock Exchange 2011-2015 period. Methods of data collection is done by using the method of documentation. Data analysis with path analysis with AMOS program version 20. The results showed the effect of variable free cash flow to debt policy is significant, effect of variable investment opportunity set against debt policy is significant, the effect of managerial ownership variable against debt policy is not significantly, the effect of variable free cash flow toward dividend policy is not significant, the effect of managerial ownership variable to dividend policy is a significant and indirect influence of the variable investment opportunity set against the dividend policy through debt policy is significant.